The Beneficial Endophytic Fungus Fusariumsolani Strain K Alters Tomato Responses Against Spider Mites to the Benefit of the Plant - Pappas, Maria L.; Liapoura, Maria; Papantoniou, Dimitra; Avramidou, Marianna; Kavroulakis, Nektarios; Weinhold, Alexander; Broufas, George D.; Papadopoulou, Kalliope K. (Frontiers in Plant Science, 2018)
Beneficial microorganisms are known to promote plant growth and confer resistance to biotic and abiotic stressors. Soil-borne beneficial microbes in particular have shown potential in protecting plants against pathogens and herbivores via the elicitation of plant responses. In this study, we evaluated the role of Fusarium solani K (FsK) in altering plant responses to the two spotted spider mite Tetranychus urticae in tomato. We found evidence that FsK, a beneficial endophytic fungal strain isolated from the roots of tomato plants grown on suppressive compost, affects both direct and indirect tomato defenses against spider mites. Defense-related genes were differentially expressed on FsK-colonized plants after spider mite infestation compared to clean or spider mite-infested un-colonized plants. In accordance, spider mite performance was negatively affected on FsK-colonized plants and feeding damage was lower on these compared to control plants. Notably, FsK-colonization led to increased plant biomass to both spider mite-infested and un-infested plants. FsK was shown to enhance indirect tomato defense as FsK-colonized plants attracted more predators than un-colonized plants. In accordance, headspace volatile analysis revealed significant differences between the volatiles emitted by FsK-colonized plants in response to attack by spider mites. Our results highlight the role of endophytic fungi in shaping plant-mite interactions and may offer the opportunity for the development of a novel tool for spider mite control.